Technology Integration in Engineering Education: Assessing Google Classroom's Effectiveness in Communication Skills Courses - Salah Zogheib, (Technium Social Sciences Journal, 2024)
This study delves into the effectiveness of Google Classroom in enhancing academic performance among first-year engineering students in a communication skills course. Rooted in the Technological Pedagogical Content Knowledge (TPACK) model and the Diffusion of Innovations theory, the research tests two hypotheses regarding the impacts of technology use and the instructor factor on student outcomes. With a sample of 356 students, the analysis employs t-tests and regression analysis to compare performance between students using Google Classroom and traditional teaching methods. The results reveal no significant difference in performance between the two groups, suggesting that integrating Google Classroom does not inherently enhance academic outcomes. However, marginal effects of instructor involvement were observed, underscoring the intricate interplay of human and technological factors in educational settings. The implications of these findings are significant, as they provide a nuanced understanding of the role of technology in education and the importance of effective instructor engagement. Future research should examine technology's role across diverse disciplines and the dynamics of instructor-student interactions within technology-enhanced environments.